Traditional Art in Building Cultural Identity: A Case Study on a Cultural Degree Event - Astuti, Yuli Tri; Cahyono, Agus; Sugiarto, Eko (Universitas Negeri Semarang, 2021)
Brebes Regency is located at the west end of Central Java, directly adjacent to Cirebon Regency, West Java Province. In general, the people in Brebes, which is known as the city of Bawang, besides being famous for its agricultural products and also very famous for its salted eggs. Brebes Regency besides being famous for its agricultural and livestock products, Brebes Regency also has various kinds of culture that developed in the Brebes people, including the arts that still exist and are still being preserved by the people of Brebes Regency namely, Burok art, Kuntulan art, Sintren art, mask art dance and lumping horses art and digul art. The art is strived for a conservation to make it easier to build a cultural identity. This study aims to determine the cultural identity built in the conservation of traditional arts in Brebes Regency through cultural degrees. The approach used to examine and explore the problem in this research is using anthropological and sociological approaches. Because they can be used to determine the process of Cultural Degree held by Brebes Regency based on the reflection of cultural values ​​for people who have human creations or historical events that have functions and people needs.